Children, adults, and shared responsibilities: Jewish, Christian and Muslim perspectives - Bunge, Marcia J. (Cambridge Univ. Press, 2012)
"This collection of essays by Jewish, Christian and Muslim scholars underscores the significance of sustained and serious ethical, interreligious and interdisciplinary reflection on children. Essays in the first half of the volume discuss fundamental beliefs and practices within the religious traditions of Judaism, Christianity and Islam regarding children, adult obligations to them, and a child's own obligations to others. The second half of the volume focuses on selected contemporary challenges regarding children and faithful responses to them. Marcia J. Bunge brings together scholars from various disciplines and diverse strands within these three religious traditions, representing several views on essential questions about the nature and status of children and adult-child relationships and responsibilities. The volume not only contributes to intellectual inquiry regarding children in the specific areas of ethics, religious studies, children's rights and childhood studies, but also provides resources for child advocates, religious leaders and those engaged in interreligious dialogue"--